Synthesis and Evaluation of Platinum Nanoparticles Using F. Carica Fruit Extract and Their Antimicrobial Activities (Baghdad Science Journal, 2023)
In this manuscript, a simple new method for the green synthesis of platinum nanoparticles (Pt NPs) utilizing F. carica Fig extract as reducing agent for antimicrobial activities was reported. Simultaneously, the microstructural and morphological features of the synthesized Pt NPs were thoroughly investigated. In particular, the attained Pt NPs exhibited spherical shape with diameter range of 5-30 nm and root mean square of 9.48 nm using Transmission Electron Microscopy (TEM) and Atomic Force Microscopy (AFM), respectively. Additionally, the final product (Pt NPs) was screened as antifungal and antibacterial agent against Candida and Aspergillus species as well as Gram-positive Staphyllococcus aureus and Gram-negative Acinetobacter species, respectively. Accordingly, the synthesized NPs demonstrated inhibition zones of 36 and 28 mm against fungal and bacterial species, respectively. The presented Pt NPs play an active role in both antifungal and antibacterial activities which indicates the presence of a well-regulated nano-materials system for biomedical application.